PEMBERDAYAAN MASYARAKAT DI WILAYAH PANIPI KECAMATAN BATUDAA KABUPATEN GORONTALO PROVINSI GORONTALO - Novianty Djafri (LP2M Universitas Bina Mandiri Gorontalo, 2018)
This KKN-PPM Program aims to empower village communities in Panipi Region Batudaa Sub-District, Gorontalo District. The specific purpose to be achieved is (1) empower village communities in Panipi Region in the fisheries development in fresh water, (2) empower village communities in Panipi Region in livestock development (cows and goats), (3) Empowering the community in developing small businesses (making cookies) and handicrafts, (4) develop the potential of the village in Panipi Region in the in the Village Owned Enterprises (BUMDes) in order to develop the economy of the village community in the PPM KKN location. Activities devotion of KKN PPM has been carried out by involving fishing communities, breeder, craftsman and all the potential of the village in Panipi Region with the empowerment model. Activities carried out by including Student of KKN PPM participants as many as 30 people through the training method, practice and assistance. In the initial stages, a team with students of KKN PPM participants make observations and identification of the potential possessed by the village in Panipi Region. In this case, include Barakati and Iluta villages which have potential and has almost the same problem. The next step is holding training and empowerment program in the fisheries development in fresh water (hold training and assistance to fishermen in repair of aquaculture techniques and provision of fish feed, and fish processing become processed food ready for consumption by the community), and livestock development (hold a training and counseling about animal health and IB technique (Artificial insemination) and develop the potential of the village through the development of Village Owned Enterprises (BUMDes) in KKN PPM location. The results of this activity are: 1) The fishing community has knowledge about aquaculture techniques and the way to make fish feed, 2) Livestock farmers community have knowledge about animal health, able to detect livestock that will be carried out the Artificial Insemination technique (IB), 3) The community able to develop all the potential of the village through the utilization of BUMDes. Training activities accompanied by students of KKN PPM Participants and involving experts from the Fishery office and Livestock office of Gorontalo District and Expert Lecturers from Faculty of Fisheries, Faculty of Animal Husbandry and Faculty of Economics, State University of Gorontalo. The final target of this activity is prepare fishing communities and breeders who are able to develop all the potential possessed by the village that becomes a location of KKN PPM, both in the field of freshwater fisheries, livestock, small business development, crafts and other business fields. Therefore, it can increase people's income